2021
DOI: 10.1111/jocs.15512
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extracorporeal membrane oxygenation in acute respiratory distress syndrome due to COVID‐19: The lessons learned from the first wave of COVID‐19

Abstract: Introduction: Extracorporeal membrane oxygenation (ECMO) has been used as a refractory treatment for acute respiratory distress syndrome (ARDS) due to coronavirus disease 2019 (COVID-19), but there has been little evidence of its efficacy.We conducted this study to share our experience using ECMO as a bridge to recovery for ARDS due to COVID-19.Methods: All adult patients who were placed on ECMO for ARDS due to COVID-19 between April 2020 and June 2020 (during the first wave of COVID-19) were identified. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“… 35 , 36 , 37 , 38 , 39 Studies were judged to be at some risk of bias for confounding adjustment and for statistical analysis and reporting if they did not account for clinically important confounders using either logistic regression or Cox proportional hazards models. 15 , 39 , 44 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 Studies reporting adjusted analyses were judged to be at some risk of bias for statistical analysis 35 , 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 if they did not adhere to methodological standards set by the PROGRESS guidelines, 19 , 20 , 21 , 22 in particular with regards to a priori selection of clinically important confounders and consideration of an appropriate sample size to minimise potential overfitting. 28 , 76 The composition and methodological quality of individual prediction models for each study and funnel plots used to evaluate for publication bias among variables that were assessed in at least ten studies are included in the appendix (p 36–41 ).…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 8 , 9 Gastrointestinal and pulmonary complications during vv-ECMO are similar to data provided in the literature. 10 12 …”
Section: Discussionmentioning
confidence: 99%
“…Because one of the main reported causes of death in this population is septic shock, identifying strategies to maximize source control and appropriate treatments of infections is paramount. 4…”
Section: The Course Of Extracorporeal Membrane Oxygenation Support In...mentioning
confidence: 99%
“…2,3 Resembling other etiologies of ARDS, the treatment of severe presentations of COVID-19 frequently involves invasive mechanical ventilation and, in most severe cases, extracorporeal membrane oxygenation (ECMO). 4…”
mentioning
confidence: 99%